2022
DOI: 10.3389/frsen.2022.1009398
|View full text |Cite
|
Sign up to set email alerts
|

Depth-resolved photochemical production of hydrogen peroxide in the global ocean using remotely sensed ocean color

Abstract: Hydrogen peroxide (H2O2) is an important reactive oxygen species (ROS) in natural waters, affecting water quality via participation in metal redox reactions and causing oxidative stress for marine ecosystems. While attempts have been made to better understand H2O2 dynamics in the global ocean, the relative importance of various H2O2 sources and losses remains uncertain. Our model improves previous estimates of photochemical H2O2 production rates by using remotely sensed ocean color to characterize the ultravio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…While 1 O 2 production was confirmed in this system with FFA ([ 1 O 2 ] ss = 2 pM) and may have contributed to the degradation of 6PPDQ, it is apparent that there is a second unknown reaction contributing to 6PPDQ attenuation in these microcosms. Previous work has reported that semiquinones, produced by the one-electron reduction of quinones, may catalyze metal-independent reduction of hydrogen peroxide to generate a hydroxyl radical. While this work focuses on photochemical pathways, future work should investigate the potential interplay between 6PPDQ redox properties and environmental photoproduction of hydrogen peroxide . To further test the hypothesis that the production of 1 O 2 in sunlit waters by dissolved organic matter may contribute to its degradation in the environment, we conducted additional experiments employing either furfuryl alcohol (FFA, 5 mM) or sodium azide (NaN 3 , 1 mM) as a 1 O 2 scavenger in SRFA microcosms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While 1 O 2 production was confirmed in this system with FFA ([ 1 O 2 ] ss = 2 pM) and may have contributed to the degradation of 6PPDQ, it is apparent that there is a second unknown reaction contributing to 6PPDQ attenuation in these microcosms. Previous work has reported that semiquinones, produced by the one-electron reduction of quinones, may catalyze metal-independent reduction of hydrogen peroxide to generate a hydroxyl radical. While this work focuses on photochemical pathways, future work should investigate the potential interplay between 6PPDQ redox properties and environmental photoproduction of hydrogen peroxide . To further test the hypothesis that the production of 1 O 2 in sunlit waters by dissolved organic matter may contribute to its degradation in the environment, we conducted additional experiments employing either furfuryl alcohol (FFA, 5 mM) or sodium azide (NaN 3 , 1 mM) as a 1 O 2 scavenger in SRFA microcosms.…”
Section: Resultsmentioning
confidence: 99%
“…31−33 While this work focuses on photochemical pathways, future work should investigate the potential interplay between 6PPDQ redox properties and environmental photoproduction of hydrogen peroxide. 34 To further test the hypothesis that the production of 1 O 2 in sunlit waters by dissolved organic matter may contribute to its degradation in the environment, we conducted additional experiments employing either furfuryl alcohol (FFA, 5 mM) or sodium azide (NaN 3 , 1 mM) as a 1 O 2 scavenger in SRFA microcosms. The attenuation rate of 6PPDQ in the presence of 1 O 2 scavengers was observed to decrease more than in the presence of the • OH scavenger isopropanol (IPA, 17.5 mM) (Figure 3c).…”
Section: Molar Absorptivity and Direct Photochemicalmentioning
confidence: 99%
“…[31][32][33] While this work focuses on photochemical pathways, future work should investigate the potential interplay between 6PPDQ redox properties and environmental photo-production of hydrogen peroxide. 34 To further test the hypothesis that the production of 1 O2 in sunlit waters by dissolved organic matter may contribute to its degradation in the environment, we conducted additional experiments employing either furfuryl alcohol (FFA, 5 mM) or sodium azide (NaN3, 1 mM) as a 1 O2 scavenger in SRFA microcosms. The attenuation rate of 6PPDQ in the presence of 1 O2 scavengers was observed to decrease more than in the presence of the •OH scavenger isopropanol (IPA, 17.5 mM) (Figure 3c).…”
Section: Molar Absorptivity and Direct Photochemical Degradation Tabu...mentioning
confidence: 99%
“…Unlike previous assessments of photochemical processes, which used a fixed AQY spectrum globally (Fichot and Miller 2010;Zhu and Kieber 2020;Zhu et al 2022), spectrally and vertically resolved DMS photolysis assessments require an additional submodel that accounts for AQY variability. Here, we used two alternative parameterizations developed using insitu datasets that encompass the wide ranges of variability of AQY and its predictors (Supplementary Table S1).…”
Section: Strengths and Limitations Of The Spectral Modelmentioning
confidence: 99%